Good farm practices and improved processing technology of enset for sustainable hunger solution in Ethiopia - Gezahagn Kudama; Tadesse Tolera; Lemane Gebeyehu (Journal of Innovation and Entrepreneurship, 2022)
Given the multi-benefits, enset cultivation has been continuously underutilized in Ethiopia. We assess best practices, processing technologies, environmental maintenance, multi-benefits of enset and its potency in hunger reduction in Ethiopia by reviewing evidence on good farm practices, improved technologies, sustainability, hunger reduction, inputs cost, and yields advantage of enset. The review results identify those best practices that optimize enset yield, technologies that facilitate extension services, processing and food qualities of enset. Moreover, we find that enset is a first-rated climate-smart crop, superior hunger solution because of its apparent capability to endure long periods (more than 5 years) of drought,~highest yield, energy food supply, and costs advantages. In contrast, its long-period maturity, cultural perceptions, and little development policy attention given to enset limit its expansion. Therefore, exploring and creating universal access mechanism of early maturing and high-yielding varieties, processing technologies and mobile-based advices, involving best practices of enset in regular agricultural extension services, changing social perceptions optimize enset yield and production thereby it contributes environmental sustainability and cuts hunger challenges.
Keywords: 650; Enset; Enset app; Environmental sustainability; Food supply; Good farm practices; Hunger; Processing technologies